INTERNASIONALISASI KAMPUS SEBAGAI STRATEGI PERGURUAN TINGGI DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Mali, Matheus Gratiano (Universitas Muhammadiyah Bengkulu, 2020)
Internationalization in the field of education is not something new in the era of globalization and then entered the era of the Industrial Revolution 4.0 and even has become a phase faced by universities both nationally and abroad in improving the quality of institutions and graduates. Collaboration and internationalization partnerships are one aspect of various educational accreditations and certifications at universities. Higher education as a scientific institution is expected to contribute significantly in efforts to help the Government to prepare human resources who have high competence, who can compete globally and that produce scientific work that is full of innovation and appropriate technology.